Semi-solid electrolyte and semi-solid lithium ion battery

By using boron-containing polymerization monomers in semi-solid lithium-ion batteries for in-situ polymerization, a solid-liquid mixed electrolyte is formed, which solves the problem of limited lithium ion transmission and significantly improves the cycling and rate performance of the battery.

CN119447440APending Publication Date: 2025-02-14ZHANGJIAGANG GUOTAI HUARONG NEW CHEM MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310949946.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The transmission of lithium ions in existing semi-solid lithium-ion batteries is limited, resulting in poor battery rate performance. How to improve the transmission capacity of lithium ions in semi-solid battery has become an urgent problem.

Method used

Boron-containing polymerized monomers are used to form a semi-solid-state electrolyte with solid-liquid mixed semi-solid electrolyte, which promotes dissociation of lithium salts by using the electron-deficient characteristics of boron atoms, and provides a lithium ion transport channel through ether oxygen units.

Benefits of technology

The cycling performance and rate performance of semi-solid lithium-ion batteries are improved, and the overall performance of the battery is improved by enhancing the transmission capacity and ion migration of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447440A_ABST
    Figure CN119447440A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-solid electrolyte and a semi-solid lithium ion battery. The invention aims to solve the problem of poor lithium ion transmission capability in the existing semi-solid lithium ion battery. The invention provides a semi-solid electrolyte, which is a solid-liquid mixture formed by reaction of a polymeric monomer in a liquid electrolyte in the presence of an initiator, and the polymeric monomer is one or more of substances shown as a structural formula (I) and a structural formula (II): # imgabs0. The lithium ion transmission capability of a lithium ion battery using the semi-solid electrolyte is improved; and the cycle performance and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a semi-solid electrolyte and a semi-solid lithium ion battery. Background Art

[0002] The in-situ conversion of liquid electrolyte into solid electrolyte by chemical methods is one of the current mainstream semi-solid battery manufacturing methods suitable for industrial mass production. Compared with other semi-solid electrolyte manufacturing methods, this method can effectively reduce the interface impedance and improve the battery cycle performance.

[0003] However, compared with the solid-liquid transport in liquid batteries, the solid-solid transport of lithium ions in semi-solid batteries is an inherent defect, which leads to limited lithium ion transport and poor battery rate performance. Therefore, how to improve the transport capacity of lithium ions in semi-solid batteries has become an urgent problem to be solved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a semi-solid electrolyte capable of improving the cycle performance and rate performance of a semi-solid lithium ion battery.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A semi-solid electrolyte, wherein the semi-solid electrolyte is a solid-liquid mixture formed by the reaction of a polymerized monomer in a liquid electrolyte in the presence of an initiator, wherein the polymerized monomer is one or more of the substances represented by structural formula (I) and structural formula (II):

[0007]

[0008] Preferably, n in the structural formula (I) and the structural formula (II) is independently selected from 1, 2, 3, 4, 5 or 6.

[0009] The structural formula (1) or structural formula (2) in the present invention can be synthesized according to the synthesis method in the art.

[0010] Preferably, the mass of the polymerized monomer is 1%-10% of the mass of the liquid electrolyte; more preferably 1%-5%; further preferably 2%-4%, for example 2%, 2.5%, 3%, 3.5%, 4%.

[0011] The amount of initiator can be adjusted appropriately according to actual needs, preferably 0.5%-5% of the mass of the polymerized monomer, more preferably 0.5%-4%; more preferably 1%-3%; and even more preferably 1%-2%. Too low an amount of initiator may result in incomplete reaction of the polymerized monomer at the polymerization temperature, and the semi-solid electrolyte cannot be formed. Too high an amount of initiator may affect battery performance.

[0012] Preferably, the initiator is a thermal initiator, and the reaction temperature is 50°C-75°C, more preferably 55°C-65°C.

[0013] Preferably, the initiator is selected from one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, and di-tert-butyl azodicarboxylate.

[0014] Preferably, the mass of the polymerized monomer is 1%-8% of the mass of the liquid electrolyte, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%.

[0015] Preferably, the mass of the initiator is 0.5%-5% of the mass of the polymerization monomer.

[0016] Preferably, the liquid electrolyte comprises an organic solvent, a lithium salt and an additive, and the mass ratio of the organic solvent, the lithium salt and the additive is (5-12):1:(0.05-1.5).

[0017] Preferably, the organic solvent consists of diethyl carbonate, ethylene carbonate, propylene carbonate and ethyl methyl carbonate.

[0018] Preferably, the lithium salt is lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0019] Preferably, the additive is one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, lithium difluorophosphate, vinyl sulfate and 1,3-propylene sultone.

[0020] Preferably, the mass ratio of diethyl carbonate, ethylene carbonate, propylene carbonate and ethyl methyl carbonate is (0.1-3):1:(0.01-1):(1-7).

[0021] Preferably, the mass of the diethyl carbonate is 5%-30% of the mass of the liquid electrolyte, for example, 5%, 10%, 15%, 20%, 25%, 30%.

[0022] Preferably, the mass of the ethylene carbonate is 10%-30% of the mass of the liquid electrolyte, for example, 10%, 15%, 20%, 25%, 30%.

[0023] Preferably, the mass of the propylene carbonate is 1%-10% of the mass of the liquid electrolyte, for example, 1%, 2%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0024] Preferably, the mass of the ethyl methyl carbonate is 30%-70% of the mass of the liquid electrolyte, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%.

[0025] Preferably, the mass ratio of the lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is (2-20):1, for example, 2:1, 5:1, 8:1, 10:1, 13:1, 15:1, 20:1.

[0026] Preferably, the mass of the lithium hexafluorophosphate is 5%-20% of the mass of the liquid electrolyte, for example, 5%, 8%, 10%, 15%, 18%, 20%.

[0027] Preferably, the mass of the lithium bis(fluorosulfonyl)imide is 1%-10% of the mass of the liquid electrolyte, for example, 1%, 2%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0028] Preferably, the mass of the additive is 1%-10% of the mass of the liquid electrolyte, for example, 1%, 2%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0029] Another object of the present invention is to provide a semi-solid lithium ion battery comprising a positive electrode, a negative electrode and a semi-solid electrolyte, wherein the semi-solid electrolyte is the above-mentioned semi-solid electrolyte.

[0030] According to some specific embodiments, the material of the positive electrode is NCM523, and the material of the negative electrode is graphite.

[0031] Another object of the present invention is to provide a method for preparing the above-mentioned semi-solid lithium ion battery, wherein the polymerized monomer, initiator and liquid electrolyte are uniformly mixed and injected into a battery comprising a positive electrode, a negative electrode and a separator to complete liquid injection and sealing, and the polymerized monomer undergoes an in-situ polymerization reaction in the liquid electrolyte to form a solid-liquid mixed semi-solid electrolyte, thereby obtaining the above-mentioned semi-solid lithium ion battery.

[0032] Preferably, the polymerization reaction temperature is 50°C-75°C, and the time is 2h-18h.

[0033] Furthermore, the polymerization reaction temperature is 55°C-65°C, and the time is 4h-10h.

[0034] Preferably, during the polymerization reaction, 0.5KG / cm 2 -3.5KG / cm 2 Pressure; preferably 0.8KG / cm 2 -2.5KG / cm 2 ; More preferably 1KG / cm 2-1.5KG / cm 2 .

[0035] Preferably, before the polymerization reaction, the battery after liquid injection and sealing is placed at 25° C.-50° C. for 12 h-48 h.

[0036] Furthermore, before the polymerization reaction, the battery after liquid injection and sealing is placed at 30° C.-40° C. for 24 h-48 h.

[0037] Due to the adoption of the above technical solution, the present invention has the following advantages compared with other processes:

[0038] The semi-solid electrolyte in the present invention adopts a boron-containing polymer monomer. Due to the electron-deficient characteristics of the boron atom, the product after the chemical reaction is still Lewis acidic and can complex anions, thereby promoting the dissociation of lithium salts, improving the lithium ion transmission capacity and the ion migration number. The polymerization product of the boron-containing polymer monomer used in the present application contains a large number of ether oxygen units, which can provide a certain lithium ion transmission capacity. The combined effect with other components in the system can further improve the cycle performance and rate performance of the semi-solid lithium ion battery. DETAILED DESCRIPTION

[0039] In existing semi-solid electrolytes, pentaerythritol tetraacrylate or pentaerythritol tetramethacrylate and other polymerized monomers are mostly used for curing, and the lithium ion transmission capacity of the formed electrolyte system needs to be further improved. To this end, after a lot of research and experimental verification, the inventors of the present application finally chose to use polymerized monomers containing boron and ether oxygen units for in-situ polymerization in liquid electrolytes, and took advantage of the electron-deficient characteristics of boron atoms. The product after the chemical reaction is still Lewis acidic and can adsorb free anions, thereby further promoting the dissociation of lithium salts and improving the lithium ion transmission capacity and ion migration number. At the same time, after the polymerization reaction of the boron-containing polymerized monomer containing ether oxygen units, the large number of ether oxygen units in the product can provide a certain lithium ion transmission capacity, and the combined effect with other components in the system can further improve the cycle performance and rate performance of the semi-solid lithium ion battery. Specifically, the polymerized monomers used in the present invention are At least one of the compounds shown.

[0040] The technical scheme of the present invention and its implementation process will be further explained below in conjunction with the embodiments and comparative examples. However, the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0041] In the present invention, unless otherwise specified, the raw materials and components in the following examples and comparative examples are all commercially available products.

[0042] [Method for synthesizing the polymerizable monomer represented by structural formula (1)]

[0043] 9.4mmol of trimethyl borate and 28mmol of poly(ethylene glycol) acrylate (when n=1, the molecular weight is 116g / mol; when n=2, the molecular weight is 160g / mol; when n=3, the molecular weight is 204g / mol; when n=4, the molecular weight is 248g / mol; when n=5, the molecular weight is 292g / mol; when n=6, the molecular weight is 336g / mol) are dissolved in 100mL of anhydrous acetonitrile, and stirred at 50°C for 3h under nitrogen to fully dissolve. Then the reaction temperature was raised to 70°C and stirred for 2h, during which nitrogen was continuously purged to eliminate by-products. Then, the unreacted reactants and acetonitrile were removed and purified by reduced pressure distillation at 50°C, and finally vacuum dried at room temperature for 2 days to obtain the desired polymerization monomers, which were named as follows:

[0044] Monomer-1-1:

[0045] Monomer-1-2:

[0046] Monomer-1-3:

[0047] Monomer-1-4:

[0048] Monomer-1-5:

[0049] Monomer-1-6:

[0050] [Method for synthesizing the polymerizable monomer represented by structural formula (2)]

[0051] 9.4mmol of trimethyl borate and 28mmol of poly(ethylene glycol) methacrylate (when n=1, the molecular weight is 130g / mol; when n=2, the molecular weight is 174g / mol; when n=3, the molecular weight is 218g / mol; when n=4, the molecular weight is 262g / mol; when n=5, the molecular weight is 306g / mol; when n=6, the molecular weight is 350g / mol;) are dissolved in 100mL of anhydrous acetonitrile, and stirred at 50°C for 3h under nitrogen to fully dissolve. Then the reaction temperature is increased to 70°C and stirred for 2h, during which nitrogen is continuously purged to eliminate by-products. Then, the unreacted reactants and acetonitrile are removed and purified by reduced pressure distillation at 50°C, and finally vacuum dried at room temperature for 2 days to obtain the desired polymerization monomers, which are named as follows:

[0052] Monomer-2-1:

[0053] Monomer-2-2:

[0054] Monomer-2-3:

[0055] Monomer-2-4:

[0056] Monomer-2-5:

[0057] Monomer-2-6:

[0058] [positive electrode]

[0059] Weigh the positive electrode material NCM523, the conductive agent acetylene black and the binder PVDF in a mass ratio of 95:2.5:2.5, add an appropriate amount of N-methylpyrrolidone, mix well, and prepare the positive electrode slurry. Spread the positive electrode slurry on aluminum foil, roll and cut it after drying to obtain the positive electrode sheet. The positive electrode compaction density is 4.15g / cm 3 .

[0060] [negative electrode]

[0061] Weigh graphite, conductive agent acetylene black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 95:2.5:2:0.5, add appropriate amount of deionized water, stir thoroughly to obtain negative electrode slurry. Apply the negative electrode slurry on copper foil, roll and cut it after drying to obtain negative electrode sheets. The compacted density of the negative electrode is 1.65g / cm 3 .

[0062] [Electrolyte formula]

[0063] The polymerization monomer, thermal initiator and liquid electrolyte are mixed evenly and prepared according to the mass ratio shown in Table 1.

[0064] Table 1 Configuration parameters of semi-solid electrolytes of Examples 1-18 and Comparative Examples 1-8

[0065]

[0066]

[0067] Note: DEC: diethyl carbonate; EC: ethylene carbonate; PC: propylene carbonate; EMC: ethyl methyl carbonate; LiPF6: lithium hexafluorophosphate; LiFSI: lithium bis(fluorosulfonyl)imide; LiDFOP: lithium difluorophosphate; VC: vinylene carbonate; PS: 1,3-propane sultone; PST: 1,3-propylene sultone; ESA: vinyl sulfate; AIBN: azobisisobutyronitrile; PETA: pentaerythritol tetraacrylate; PTMEA: pentaerythritol tetramethacrylate.

[0068] [Battery manufacturing]

[0069] Using the above-mentioned positive electrode, negative electrode and electrolyte, a PE separator with a thickness of 12 microns is selected, and a lamination process is adopted to manufacture a soft-pack battery with a designed capacity of 1800 mAh.

[0070] After the battery is filled and sealed, it is placed at 35°C for 36 hours to ensure that the electrolyte completely soaks the positive and negative electrode materials. It is then placed in a 60°C environment for 6 hours and the battery is subjected to 1.2KG / cm 2 The liquid electrolyte is converted into a semi-solid electrolyte in situ under pressure.

[0071] [Battery performance test]

[0072] The battery cycle performance test was conducted at 25°C and 0°C, with a voltage range of 3-4.25V. The battery was charged and discharged at a rate of 1C, and the capacity retention rate after 1000 cycles was tested. Capacity retention rate (%) = (discharge capacity after 1000 cycles / discharge capacity after the first cycle) × 100%.

[0073] The rate performance test was conducted at 25°C with a voltage range of 3-4.25V. After the battery was cycled at 0.2C for three weeks, it was then tested at a rate discharge current of 3C. The discharge capacity was recorded after each rate discharge. 3C rate discharge retention rate = (3C discharge capacity / 0.2C discharge capacity) × 100%.

[0074] Table 2 Normal temperature / low temperature cycle performance and rate performance of semi-solid lithium-ion batteries

[0075]

[0076]

[0077] Table 2 shows that the electrochemical performance of the boron-containing polymer monomer is better than that of the boron-free polymer monomer (pentaerythritol tetraacrylate or pentaerythritol tetramethacrylate). This is because the boron-containing polymer monomer itself lacks electrons and is Lewis acidic, which can adsorb free anions, thereby further promoting the dissociation of lithium salts, improving the lithium ion transmission capacity and ion migration number, and thus improving the lithium ion rate and cycle performance.

[0078] Table 2 also shows that as the length of the polymerized monomer chain increases, the ether oxygen units gradually increase, and the polymerized product provides additional lithium ion transmission channels, synergizing with the liquid electrolyte to improve the battery's cycle and rate performance, with n = 4, that is, 4 ether oxygen units on the chain being the best. As the chain length increases further, the distance of lithium ion transition or transfer on the polymerized product increases, resulting in the inhibition of lithium ion transmission and the deterioration of battery performance.

[0079] Table 2 also shows that with the increase of monomer content, the degree of polymerization gradually increases, and the two-phase lithium ion transmission channel is gradually formed, and they work synergistically with each other to improve the battery cycle and rate performance, with the best monomer addition amount being 3%; with the further increase of monomer content, the mechanical strength of the semi-solid electrolyte gradually increases, lithium ion transmission is hindered, and battery performance deteriorates.

[0080] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A semi-solid electrolyte, characterized in that: The semi-solid electrolyte is a solid-liquid mixture formed by the reaction of polymerized monomers in a liquid electrolyte in the presence of an initiator, and the polymerized monomers are one or more substances represented by structural formula (I) and structural formula (II):

2. The semi-solid electrolyte according to claim 1, characterized in that: In the structural formula (I) and the structural formula (II), n is independently selected from 1, 2, 3, 4, 5 or 6.

3. The semi-solid electrolyte according to claim 1, characterized in that: The mass of the polymerized monomer is 1%-10% of the mass of the liquid electrolyte.

4. The semi-solid electrolyte according to claim 1, characterized in that: The mass of the initiator is 0.5%-5% of the mass of the polymerization monomer.

5. The semi-solid electrolyte according to claim 4, characterized in that: The initiator is a thermal initiator, and the reaction temperature is 50°C-75°C; And / or, the initiator is selected from one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, and di-tert-butyl azodicarboxylate.

6. The semi-solid electrolyte according to claim 1, characterized in that: The liquid electrolyte comprises an organic solvent, a lithium salt and an additive, wherein the mass ratio of the organic solvent, the lithium salt and the additive is (5-12):1:(0.05-1.5).

7. The semi-solid electrolyte according to claim 6, characterized in that: The organic solvent is composed of diethyl carbonate, ethylene carbonate, propylene carbonate and ethyl methyl carbonate; And / or, the lithium salt is lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; And / or, the additive is one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, lithium difluorophosphate, vinyl sulfate and 1,3-propylene sultone.

8. The semi-solid electrolyte according to claim 7, characterized in that: The mass ratio of diethyl carbonate, ethylene carbonate, propylene carbonate and ethyl methyl carbonate is (0.1-3):1:(0.01-1):(1-7); And / or, the mass of the diethyl carbonate is 5%-30% of the mass of the liquid electrolyte; And / or, the mass of the ethylene carbonate is 10%-30% of the mass of the liquid electrolyte; And / or, the mass of the propylene carbonate is 1%-10% of the mass of the liquid electrolyte; And / or, the mass of the ethyl methyl carbonate is 30%-70% of the mass of the liquid electrolyte; and / or, the mass ratio of the lithium hexafluorophosphate to the lithium bis(fluorosulfonyl)imide is (2-20):1; And / or, the mass of the lithium hexafluorophosphate is 5%-20% of the mass of the liquid electrolyte; And / or, the mass of the lithium bis(fluorosulfonyl)imide is 1%-10% of the mass of the liquid electrolyte; And / or, the mass of the additive is 1%-10% of the mass of the liquid electrolyte.

9. A semi-solid lithium ion battery comprising a positive electrode, a negative electrode and a semi-solid electrolyte, characterized in that: The semi-solid electrolyte is the semi-solid electrolyte according to any one of claims 1 to 8.

10. The method for preparing a semi-solid lithium-ion battery according to claim 9, characterized in that: The polymerized monomer, initiator and liquid electrolyte are mixed evenly and injected into a battery including a positive electrode, a negative electrode and a separator to complete the liquid injection and sealing. The polymerized monomer undergoes an in-situ polymerization reaction in the liquid electrolyte to form a solid-liquid mixed semi-solid electrolyte, thus obtaining the semi-solid lithium ion battery.